Hexapod robot for autonomous machining - Saleh, Tanveer; Khan, Md. Raisuddin (IOP Publishing Ltd, 2019)
Product miniaturization is a key aspect of manufacturing nowadays. Computer numerically controlled (CNC) machine tools are the major tools used in manufacturing industries for producing miniaturized products. However, CNC machines are still big, bulky and stationary. This research is an effort to develop a modular machine on a robotic platform which would be able to carry out machining operation. Hexapod robots are mobile, small and stable robots which are developed having a lot of variety. In this project a Hexapod robot was designed and fabricated for machining operation. The research scope for this project was limited to 1-D machining i.e. drilling operation. A suitable existing robot (hexapod) design was followed in this project. A drilling spindle was attached with the robot to carry out the machining operation. The robot was controlled using serial communication. A GUI (Graphical User Interface) was developed to control the Hexapod which had all the required algorithm inside. Machining operations were carried out with the prototype robot to test its performance. The highest accuracy was found using spindle speed of 2500RPM and velocity of 200mm/min. The repeatability found using these parameters were around 25micron. The positional accuracy of the robot movement was compared with that of an existing commercial micromachining system. The performance of the robot was found to be almost similar to that of the commercial machine.